056 Efficacy of fremanezumab in chronic migraine patients with inadequate response to ≥3 preventive medication classes. Issue 6 (27th May 2022) - Lambru, Giorgio; Dhiraj, Dalbir; Ning, Xiaoping; Campos, Verena Ramirez; Barash, Steve; Sherwin, Eoin; Cohen, Joshua
Abstract : Objective: To evaluate efficacy of fremanezumab in a subgroup of chronic migraine (CM) patients with inadequate response to ≥3 migraine preventive medication classes (CM ≥3 inadequate responses subgroup) from the double-blind, phase 3b FOCUS study. Methods: In FOCUS, patients with inadequate response to 2–4 migraine preventive treatment classes were randomized (1:1:1) to quarterly fremanezumab, monthly fremanezumab, or placebo for 12 weeks. Changes in monthly migraine days (MMD), 6-item Headache Impact Test (HIT-6) score, and monthly days using acute headache medication and response rates (≥30% reduction in MMD), were evaluated in CM ≥3 inadequate responses subgroup. Results: Of 838 randomized patients, 293 were included in this analysis. Change from baseline in MMD over 12 weeks was significantly greater with fremanezumab (LSM[SE]: quarterly, −4.0[0.56]; monthly, −4.1[0.56]) versus placebo (−1.0[0.59]; P<0.0001), as was ≥30% response rate (44% and 46% vs 18%; P<0.0001). Signifi- cantly greater reductions from baseline were observed in HIT-6 scores during 4 weeks after third study- drug dose with quarterly (−3.8[0.70]) and monthly (−4.9[0.71]) fremanezumab versus placebo (−1.7[0.75]; P<0.01). Reductions in acute medication use days were significantly greater with fremanezumab versus placebo (P<0.0001). Conclusions: In CM patients with inadequate response to ≥3 migraine preventive medication classes, fremanezumab was well tolerated and effective. mknagge@cellohealth.com 53